Novel of neodymium nanoparticles zinc tellurite glasses in experimental and theoretical elastic properties using artificial intelligence approach - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2023)
Novel of neodymium nanoparticles zinc tellurite glasses in experimental and theoretical elastic properties using artificial intelligence approach by Muhammad Noorazlan Abd Azis